Neural representation of action symbols in primate frontal cortex - Lucas Y. Tian; Kedar Garzón Gupta; Daniel J. Hanuska; Adam G. Rouse; Mark A. G. Eldridge; Marc H. Schieber; Xiao-Jing Wang; Joshua B. Tenenbaum; Winrich A. Freiwald (Nature, 2026)
Abstract A hallmark of intelligence is proficiency in solving new problems, including those that substantially differ from previously seen problems. Problem solving in turn depends on the goal-directed generation of novel ideas and behaviours 1 , which has been proposed to involve internal representations of discrete units (or symbols) that can be recombined into numerous possible composite representations 1–7 . Although this view has been influential in cognitive-level explanations of behaviour, definitive evidence for a neuronal substrate of symbols has remained elusive. Here we identify a neural population that encodes action symbols—recombinable representations of discrete units of motor behaviour—in a specific area of the frontal cortex. In macaque monkeys performing a drawing-like task, we found behavioural evidence that action elements (strokes) exhibit three crucial features that indicate an underlying symbolic representation: (1) invariance over low-level motor parameters; (2) categorical structure, which reflects discrete action types; and (3) recombination into novel sequences. Based on simultaneous neural recordings across eight regions of the motor, premotor and prefrontal cortex, we identified population activity specifically in the ventral premotor cortex that encodes planned actions in a manner that also reflects invariance, categorical structure and recombination. These findings reveal a neural representation of action symbols localized to the ventral premotor cortex and a putative neural substrate for symbolic operations.